A new species of the genus Navicordulia Machado & Costa, 1995 from Ecuador (Insecta: Odonata: Corduliidae s.str.) - Fleck, Günther; Haber, William A. (Zootaxa, 2025)
Based on a single male specimen a new species of the genus Navicordulia Machado & Costa, 1995 from Ecuador is described and illustrated, representing the first described species for this country. The recent considerable westward expansion of the distribution of the genus is briefly discussed. The male of Navicordulia tangoyi sp. nov. can be separated from its congeners by the distinct shape and pilosity of the genital lobe and by the remarkable deflection of the distal fourth of the cerci. A differential diagnosis and an updated key to all known males of the genus are provided.